“Blackness, Blood, and Borders:” Anti-Black Racism in Disabled Children’s Health Care Spaces as Epistemic Violence - Moola, Fiona J.; Johnson, Kathia; Moothathamby, Nivatha (Journal of Childhood Studies, 2026)
The lives, selves, and social worlds of racialized disabled children and their parents have been hidden and silenced under the weight of grand metanarratives about the white disabled child. In this way, the centrality of the white disabled Eurocentric child is a symbolic violence that has erased the lives of other children, especially Black children and their families. In this qualitative interpretive study, we utilized a theoretically informed approach to explore the parenting journeys of Black parents who care for disabled children. We found that anti-Black racism, as symbolic violence, was constituted by health care narratives about biological determinism. Health systems also symbolically violated the lives of Black mothers through practices of bodily control and surveillance, and the wisdom and generational knowledge of Black mothers as experts on their children’s lives was erased through the practice of being rendered incompetent. Implications: Following calls by Black feminists, we suggest that scholars, theorists, and clinicians must theoretically and empirically center the lives of Black mothers with disabled children while recognizing the grave harms of anti-Black racism in children’s hospital spaces.